The Story of Carmen in the Lens of the Locals: Basis for a Biographical Sketch of Carmen through Narrative Interview derived from Maslow’s Hierarchy of Needs and Sigmund Freud’s Psycho-sexual Theory: Kisah Carmen dalam Perspektif Masyarakat Lokal: Dasar untuk Sketsa Biografi Carmen melalui Wawancara Naratif berdasarkan Hirarki Kebutuhan Maslow dan Teori Psiko-seksual Sigmund Freud - Intico, Ruth Mesha A.; Alumnia, Christine; Omambac, Mitch John Claude; Tulio, Ronelyn; Bonganciso, Ruel; Normandia, John Jonathan (Journal of Literature and Education, 2025)
This study is conducted to determine the story of Carmen based on the lens of local. Narrative Inquiry is used to make the participants tell the story rather than answer the questions given. The study tackles the people connected to Carmen, places she had been, conflict in the story and themes and message that can be derived using Abraham Maslow’s Hierarchy of Needs and Sigmund Freud’s Psychosexual Stage. In the beginning, Carmen’s basic needs are met since she’s part of a rich family with everything provided for her. But despite her material wealth, she’s lacking emotional connection and love. She feels isolated and longs to belong. Carmen’s desire for love and intimacy clashes with her family’s expectations and societal norms. She’s torn between her desires and the need for esteem and acceptance from her family. Her story teaches us to balance our desires with societal expectations and not to neglect our emotional needs for the sake of material wealth and status. Also, this study aims to preserve the story for future generations and promote tourism in Cadiz City.